2011
DOI: 10.1080/15524256.2011.623471
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Critical Illness: A Case Study in Ambiguity

Abstract: Social workers address issues of critical illness and end of life in multiple settings. Due to advances in medical technology, an increasing number of patients survive severe critical illnesses. Little is known about the psychological dynamics of these patients who recover from critical illness and move into the liminal space between life and death. In this article the author analyzes the psychological ambiguities present during recovery from critical illness. Using a case study, connections will be made betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In essence, liminality explicates the experiences of ICU survivors’ transitions, including their inherent uncertainty and it is this aspect that is of interest to ICU survivorship. Interestingly, whilst living in and through a liminal time can be very challenging for ICU survivors, the inherent uncertainty also creates space and opportunities for growth and personal development (Johnston ).…”
Section: Findings and Discussion: Transitioning To Icu Survivorshipmentioning
confidence: 99%
“…In essence, liminality explicates the experiences of ICU survivors’ transitions, including their inherent uncertainty and it is this aspect that is of interest to ICU survivorship. Interestingly, whilst living in and through a liminal time can be very challenging for ICU survivors, the inherent uncertainty also creates space and opportunities for growth and personal development (Johnston ).…”
Section: Findings and Discussion: Transitioning To Icu Survivorshipmentioning
confidence: 99%
“…The lens of liminality has been used to describe the experience of individuals facing critical or life‐threatening illness or injury (Blows, Bird, Seymour, & Cox, ; Bruce et al, ; Johnston, ; Mwaria, ). Johnston () used the theory of liminality to describe the ambiguity experienced by a single patient recovering from a critical illness who felt marginalized living in a stressful, uncertain space where one cannot plan for the future. Blows et al (), in a narrative review of 10 studies of cancer patients, concluded that liminality accurately described the experience of the cancer trajectory.…”
mentioning
confidence: 99%
“…Halucinatory experiences appear to be common for ICU patients. Johnston (2011 :373) describes these experiences as “a developmental mechanism which the patient’s mind is using to process psychological issues”. Francine’s first memories after discharge from the ICU corresponds with literature ( Johnston, 2011 ; Jones, Griffiths, & Humphris, 2000 ; Papathanassoglou & Patikari, 2003 ; Richman, 2000 ; Wallen, Chaboyer, & Thalib, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Illness and trauma are challenges that involve the individual as a totality. Little is known about the psychosocial dynamics of a patient who recovers from critical illness and the psychological impact of the ICU experiences have not been fully investigated ( Johnston, 2011 ). It is only since the 1990’s that authors began to describe the delirium, hallucinations and post-traumatic stress disorder symptoms experienced by ICU patients ( Johnston, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation